2012
DOI: 10.1002/ps.3246
|View full text |Cite
|
Sign up to set email alerts
|

Development of a rapid resistance monitoring bioassay for codling moth larvae

Abstract: The results presented here demonstrate that a novel and rapid bioassay can be used to monitor for codling moth resistance to methoxyfenozide. The bioassay method is relevant to both ingestion and contact insecticides, but a single diagnostic dose, regardless of larval age, is only relevant to ingestion insecticides. Age-dependent diagnostic doses are likely necessary for contact insecticides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This finding may suggest a cross‐resistance with organophosphates, particularly azinphos‐methyl (heavily used before 2008) and phosmet, which was suitably demonstrated in previous works . Cross‐resistance of methoxyfenozide with organophosphates has been demonstrated by several authors in codling moth (in North Carolina, USA, in Michigan, USA and in Canada) and other tortricid pests [obliquebanded leafroller, Choristoneura rosaceana (Harris) in New York, USA, and Michigan, USA, and Planotortrix octo Dugdale in New Zealand] . The Spanish field populations resistant to methoxyfenozide were susceptible to tebufenozide but the French population tolerant to methoxyfenozide was also tolerant to tebufenozide.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This finding may suggest a cross‐resistance with organophosphates, particularly azinphos‐methyl (heavily used before 2008) and phosmet, which was suitably demonstrated in previous works . Cross‐resistance of methoxyfenozide with organophosphates has been demonstrated by several authors in codling moth (in North Carolina, USA, in Michigan, USA and in Canada) and other tortricid pests [obliquebanded leafroller, Choristoneura rosaceana (Harris) in New York, USA, and Michigan, USA, and Planotortrix octo Dugdale in New Zealand] . The Spanish field populations resistant to methoxyfenozide were susceptible to tebufenozide but the French population tolerant to methoxyfenozide was also tolerant to tebufenozide.…”
Section: Discussionmentioning
confidence: 57%
“…A number of codling moth insecticides classified as reduced‐risk or OP alternatives have been registered in Spain since the 1980s and are recommended by IPM programs: the insect growth regulator fenoxycarb, the neonicotinoid thiacloprid, the ecdysone receptor agonists methoxyfenozide and tebufenozide, the voltage‐dependent sodium channel blocker indoxacarb, the nicotinic acetylcholine receptor allosteric modulator spinosad and, recently, the ryanodine receptor modulator chlorantraniliprole. Codling moth cross‐resistance among some of these reduced‐risk insecticides groups and OPs and pyrethroids have been detected in some European countries, the USA and Canada, even with pesticides that have been registered recently or have not yet been registered . No codling moth susceptibility study has been reported investigating these new chemical insecticides, with the exception of thiacloprid, which has been tested in Spanish field populations, with studies showing generally high levels of enzymatic detoxification, attributable mainly to cytochrome P450 polysubstrate monooxygenases (PSMOs) (in neonate larvae, adults and post‐diapausing larvae), but also to glutatione S‐transferases (GSTs) (in adults and post‐diapausing larvae) and esterases (ESTs) (in post‐diapausing larvae) …”
Section: Introductionmentioning
confidence: 99%
“…Baseline field surveys for resistance in tortricid populations have been conducted with several classes of insecticides across most geographical areas of these pests using a variety of bioassay approaches (Knight et al 1994(Knight et al , 2001aSauphanor et al 2000;Pasquier and Charmillot 2003;Knight 2010b). In some cases significant differences among bioassay methods suggested the need to standardize methodologies (Sauphanor et al 1998a;Reyes and Sauphanor 2008;Magalhaes et al 2012). In response, standardized surveys have been conducted across large geographical areas (Reyes et al , 2009).…”
Section: Insecticide Programmesmentioning
confidence: 99%
“…Populations were synchronized in age structure in spring owing to the age-homogenizing effect of diapause induced by photoperiod during the preceding fall. 16 Resistance classification of codling moth populations was based on resistance bioassay results 17,18 and knowledge of the response of populations to field applications of insecticides. Not every orchard population was tested for resistance, but the history of insecticide use and knowledge of the level of field control obtained with various insecticides was available for each orchard.…”
Section: Trapping Datamentioning
confidence: 99%